Area under the curve achievement of once daily tobramycin in children with cystic fibrosis during clinical care. Issue 12 (3rd September 2020) - Brockmeyer, Jake M.; Wise, Russell T.; Burgener, Elizabeth B.; Milla, Carlos; Frymoyer, Adam
Abstract: Background: The area under the concentration‐time curve over 24 hours (AUC24 ) is frequently utilized to monitor tobramycin exposure in children with cystic fibrosis (CF). An understanding of exposure target achievement during clinical implementation of an AUC24 based approach in children is limited. Methods: A retrospective chart review was performed in children with CF treated with once daily tobramycin and drug concentration monitoring at a pediatric CF center. During clinical care AUC24 was estimated using a traditional log‐linear regression approach (LLR). AUC24 was also estimated retrospectively using a pharmacokinetic model‐based Bayesian forecasting approach (BF). AUC24 achievement after both approaches were compared. Results: In 77 treatment courses (mean age, 12.7 ± 5.0 years), a target AUC24 100 to 125 mg h/L was achieved after starting dose in 21 (27%) and after initial dose adjustment in 35 (45%). In the first 7 days of treatment, 24 (32%) required ≥3 dose adjustments, and the mean number of drug concentrations measured was 7.1 ± 3.2. Examination of a BF approach demonstrated adequate prediction of measured tobramycin concentrations (median bias −2.1% [95% CI −3.1 to −1.4]; median precision 7.6% [95% CI, 7.1%‐8.2%]). AUC24 estimates utilizing the BF approach were higher than the LLR approach with a mean difference of 6.4 mg h/L (95% CI, 4.8 to 8.0 mg h/L). Conclusions: Achievement of a narrow AUC24 target is challenging during clinical care, and dose individualization is needed in most children with CF. Implementing a BF approach for estimating AUC24 in children with CF is supported.